The stability of the soil slope at the entrance of Edu Hub Pagoh – A case study - Suwandi, Amir Khan; Aznil, Ammirul Ikhwan; Abd Aziz, Muhammad Danial Fakhri; Norsham, Nor Iskandar; Abdullah, Noorul Hudai (Multidisciplinary Applied Research and Innovation, 2021)
Slopes whether natural or man-made can be analyzed their stability in various ways and methods. In this study by using several slope features such as the soil type, soil stratification, groundwater, seepage and slope dimensions [1] to estimate its stability. The use of field data to identify possible failure modes or to locate most possible slip surfaces of soil slopes is the challenge in the slope analyzation in this study [2]. In order to estimate the safety factor of the chosen slope at entrance of Edu Hub Pagoh, soil samples were taken from six sites to be analysed. Disturbed and undisturbed soil were taken at three locations left and right of the road by using core cutter. All tests such as shear strength and the soil classification through the common test such as sieve analysis test, plastic limit test (PL), liquid limit test (LL), and specific gravity test (SG) were conducted on all soil samples. The results is the relationship between shear stress and normal stress are linearly increase. Soil parameters; namely, unit weight, shear strength (in terms of c and Ø values) are used in performing the Geoslope Software in calculating the safety factors of the slopes.